W oczekiwaniu na niepodległość. Bydgoszcz w latach 1918-1919 (Tabularium Historiae, 2021)
At the end of World War I, the majority of Germans and Poles from Bydgoszcz felt uncertainty as to what would happen next. The attitudes of the German and Polish populations were, however, radically different. President Wilson’s message of January 8, 1918 aroused hope in Poles. Poles from Bydgoszcz began preparations to take over power in the city. At the same time, the prospect of Bydgoszcz finding itself within the borders of the Polish state evoked feelings of uncertainty and depression among the German inhabitants of Bydgoszcz. Poles waited for the decisions of the peace conference in Paris. On November 16, 1918, the Polish People’s Council was established for the city of Bydgoszcz and its vicinity, which became the official representative of the Polish population. On June 28, 1919, the German delegation in Versailles signed a peace treaty. Bydgoszcz’s return to Poland a fact.